2021
DOI: 10.20473/j.djmkg.v54.i2.p57-62
|View full text |Cite
|
Sign up to set email alerts
|

The effect of 3% binahong leaf extract gel on the wound healing process of post tooth extraction

Abstract: Background: One of the common frequently performed procedures in dentistry is tooth extraction. After tooth extraction, a series of biological events occurs in the alveolar socket that ultimately results in healing of the socket. Binahong (Anredera cordifolia) is an herbaceous plant that contains active compounds that may accelerate the wound healing process. Purpose: The aim of this study is to investigate the effect of 3% binahong leaf extract gel on the healing process of the postextraction wound. Methods: … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
21
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(22 citation statements)
references
References 20 publications
1
21
0
Order By: Relevance
“…4,5 Healing after tooth extraction consists of three phases, namely the inflammatory phase, the proliferative phase, and the remodeling phase. 6 The healing process after tooth extraction begins with the presence of a blood clot that clogs the broken blood vessel to stop the bleeding. In the inflammatory phase, the wound area will be dominated by inflammatory cells, namely neutrophils and macrophages that have a phagocytic function and the release of growth factors that will stimulate the proliferation and differentiation of osteoprogenitor cells into osteoblasts on the 5th day after tooth extraction.…”
Section: Introductionmentioning
confidence: 99%
“…4,5 Healing after tooth extraction consists of three phases, namely the inflammatory phase, the proliferative phase, and the remodeling phase. 6 The healing process after tooth extraction begins with the presence of a blood clot that clogs the broken blood vessel to stop the bleeding. In the inflammatory phase, the wound area will be dominated by inflammatory cells, namely neutrophils and macrophages that have a phagocytic function and the release of growth factors that will stimulate the proliferation and differentiation of osteoprogenitor cells into osteoblasts on the 5th day after tooth extraction.…”
Section: Introductionmentioning
confidence: 99%
“…12 In addition, if, after tooth extraction, the wound fails in one of the healing phases, especially in the angiogenesis process, the wound cannot heal properly. 13 Drugs can reduce complications and speed up the wound recovery process after tooth extraction. Complications may occur in inadequate tooth extraction.…”
Section: Introductionmentioning
confidence: 99%
“…One of the non-steroidal anti-inflammatory drugs that is often used after tooth extraction is diclofenac. Nevertheless, previous studies reported that diclofenac administration could inhibit the formation of blood clots and fibroblasts; 12,13 therefore, an alternative drug to minimize the side effects of diclofenac administration is necessary. Purple leaves are known as plants with anti-inflammatory effects and have been reported to increase the number of fibroblasts in rats induced by Porphyromonas gingivalis in their sulcus.…”
Section: Introductionmentioning
confidence: 99%
“…as antimicrobials work by inhibiting the synthesis of proteins, lipids, and bacterial DNA. Not only that, saponins which are anticarcinogenic and antiseptic can inhibit the growth of microorganisms present in the wound, so it does not aggravate wound infection 15,16. Other content in saponins also plays a role in increasing the proliferation of fibroblast cells.…”
mentioning
confidence: 99%
“…The mechanism of action of saponins in ulcer healing is by stimulating the production of type I collagen which has an important role in the wound closure process and increases the speed of tissue epithelialization 5. Saponins obtained after extracting binahong leaves act as angiogenetic agents that can increase cell activity in the formation of blood vessels during the proliferative phase of wound healing 15. In research conducted byHanafiah et al (2019) observed the proliferative activity of fibroblast cells 3T3 5.…”
mentioning
confidence: 99%